2022
DOI: 10.3390/app12136558
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Content, Lipid Quality Indices, and Mineral Composition of Cow Milk and Yogurts Produced with Different Starter Cultures Enriched with Bifidobacterium bifidum

Abstract: This study aimed to analyze the composition of fatty acids, with particular emphasis on the content of cis9trans11 C18:2 (CLA) acid, the content of minerals, and lipid quality indices in raw milk, pasteurized milk, and in yogurts produced with selected starter cultures enriched with Bifidobacterium bifidum. The GC-FID method was used to determine the fatty acid composition of those dairy products. To analyze the contents of microelements (copper, manganese, iron, and zinc) and macroelements (magnesium, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
3
8
0
1
Order By: Relevance
“…Since that discovery, studies have revealed that omega-3 fatty acids are also effective against cancer, inflammatory bowel disease, rheumatoid arthritis, psoriasis, and rheumatoid factors. Our results are consistent with those reported by Paszczyk and Tonska [ 32 ]; they illustrated that utilizing cultures enriched with Bifidobacterium bifidum (BB-12) in yogurt preparation increased the content of conjugated linolenic acid compared with that made using cultures free from BB-12.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Since that discovery, studies have revealed that omega-3 fatty acids are also effective against cancer, inflammatory bowel disease, rheumatoid arthritis, psoriasis, and rheumatoid factors. Our results are consistent with those reported by Paszczyk and Tonska [ 32 ]; they illustrated that utilizing cultures enriched with Bifidobacterium bifidum (BB-12) in yogurt preparation increased the content of conjugated linolenic acid compared with that made using cultures free from BB-12.…”
Section: Resultssupporting
confidence: 93%
“…paracasei SE160 and VC213, Lactobacillus plantarum VS166 and VS513, Lactobacillus casei VC199, Enterococcus lactis BT161, and Enterococcus faecium VC223) had the capability to reduce cholesterol in cheese. However, Paszczyk and Tonska [ 32 ] reported that the levels of atherogenicity index, index thrombogenicity, and hypocholesterolemic/hypercholesterolemic (the lipid quality indices) were similar in yogurt sample produced by cultures enriched with or without BB-12.…”
Section: Resultsmentioning
confidence: 99%
“…Minerals content of raw, evaporated and concentrated milk were investigated and the obtained data showed in Table (4). From the showed results in this Table could be noticed that potassium is the most prevalent mineral, with the significant highest value recorded 848.1 ppm followed by sodium 653.7 ppm then calcium ranked third among minerals, where its value was 289.7 ppm while value of phosphorous and magnesium were 97.2 and 61.36 ppm, these results were similar with the results obtained by [36,37], who reported that the relative concentrations of minerals can significantly vary due to a number of factors such as species, breed, nutritional status of animal, stage of lactation, health condition of animal and season of the year. Also, the results indicated a significant increase in the mineral content in both (EM) and (CM) compared to (RM) where the values were as follows: Mg 72.93 and 84.42 ppm, Na 763.7 and 787.6 ppm, K 988 and 1125 ppm, P 125.8 and 136.1 ppm and Ca 325.9 and 373.8 ppm respectively, These results were consistent with [38,39], and this due to that removing moisture from milk leads to an increase in the percentage of ash, and thus a rise in the percentage of minerals as one of the most important components of ash [40], It is compatible with the data mentioned in Table (4) where the decrease in moisture caused an increase in the percentage of ash from 0.67% at (RM) to 0.88 and 0.96% at (EM) and (CM) respectively.…”
Section: Minerals Content Of Raw Evaporated and Concentrated Milksupporting
confidence: 79%
“…The lipid pro le of yogurt is an important factor affecting its nutritional and sensory quality (Paszczyk & Tońska, 2022). The present study revealed a slight (p>0.05) decrease in the total fat content (MGT) of the products over the storage period.…”
Section: Yogurt Fatty Acidmentioning
confidence: 45%